2014
DOI: 10.1016/j.minpro.2014.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Surface chemistry aspects of bastnaesite flotation with octyl hydroxamate

Abstract: Surface chemistry features of bastnaesite were investigated with respect to octyl hydroxamate adsorption and the wetting characteristics at different levels of hydroxamate adsorption. The wetting characteristics of bastnaesite in the absence of collector adsorption were examined using both contact angle measurements and MD simulations. As expected, it was found that bastnaesite is naturally hydrophilic. Surface chemistry studies included octyl hydroxamate adsorption by the solution depletion method. The surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
30
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(32 citation statements)
references
References 29 publications
2
30
0
Order By: Relevance
“…Based on the ionic radii of elements, REEs can be classified into light rare earth elements (LREEs) from La to Sm, and heavy rare earth elements (HREEs) from Eu to Lu [1,2]. REEs are crucial to manufacturing of many advanced products and have broad commercial applications, such as new catalysts for automotive exhaust systems, permanent magnets for computer equipment, medical diagnosis equipment, and almost all military systems [3,4]. A semi-soluble salt mineral with the characteristics of ionic bonding and limited solubility in water, bastnaesite, (Ce, La)FCO 3 , is a complex rare earth fluoride and carbonate salt and contains the cerium subgroup or the lighter rare earth elements.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the ionic radii of elements, REEs can be classified into light rare earth elements (LREEs) from La to Sm, and heavy rare earth elements (HREEs) from Eu to Lu [1,2]. REEs are crucial to manufacturing of many advanced products and have broad commercial applications, such as new catalysts for automotive exhaust systems, permanent magnets for computer equipment, medical diagnosis equipment, and almost all military systems [3,4]. A semi-soluble salt mineral with the characteristics of ionic bonding and limited solubility in water, bastnaesite, (Ce, La)FCO 3 , is a complex rare earth fluoride and carbonate salt and contains the cerium subgroup or the lighter rare earth elements.…”
Section: Introductionmentioning
confidence: 99%
“…REEs are crucial to manufacturing of many advanced products and have broad commercial applications, such as new catalysts for automotive exhaust systems, permanent magnets for computer equipment, medical diagnosis equipment, and almost all military systems [3,4]. A semi-soluble salt mineral with the characteristics of ionic bonding and limited solubility in water, bastnaesite, (Ce, La)FCO 3 , is a complex rare earth fluoride and carbonate salt and contains the cerium subgroup or the lighter rare earth elements. Bastnaesite is considered as one of the most important sources of rare earth elements because of its richness in the light rare earth elements and its large global reserves [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Density functional theory (DFT) computation indicated that the dianion of cyclohexyl hydroxamic acid (CHA) or benzoylhydroxamic acid (BHA) exhibited stronger chemical reactivity than their anions and neutral molecules, and that the replacement of the phenyl group by the cyclohexyl group in the BHA molecule significantly impacted the electron donating ability of hydroxamate collectors [12]. Through studying the surface chemistry features of bastnaesite with respect to octyl hydroxamate adsorption, sum-frequency vibrational spectroscopy (SFVS) spectra indicate that a well-ordered monolayer was formed at a hydroxamate concentration of about 1 × 10 −4 mol/L [13]. Meanwhile, some studies reported the chelating behavior of salicylaldoxime on oxide minerals, which is an O-N type chelating reagent.…”
Section: Introductionmentioning
confidence: 99%
“…Also, in comparison with alkaline earth metals, which are present as associated gangue minerals, REE cations are preferential coordination centers for hydroxamate complex formation [16]. The collector's interaction with bastnäsite and monazite has been recognized to manifest as a chemisorption in which hydroxylated REEs re-adsorb at the mineral surface prior to interact with hydroxamate through anion exchange to form stable REE surface complexes [14,[18][19][20]. Moreover, it has been reported that redox chemistry plays an important role in the superior beneficiation of bastnäsite using an alkyl hydroxamic acidcontaining collector over other flotation collectors such as fatty acids.…”
Section: Introductionmentioning
confidence: 99%